Genetic diversity in F2 segregating population of different commercial hybrids of tomato (Solanum lycopersicum L.) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 43-48